Mathématiques
DannoO
13

Bonjour j'ai cet exercice à faire: 1) A (x) = (x+1)au carré + 5(1-2x) 2) (x)= (2x-3)(3x+1) - 2 (x+4) 3) C(x) = (2x-3) au carré + (3-2x) (1-x) Merci d'avance.

+1
(2) Réponses
hanakhan

Bonjour A= (x+1)²+5(1-2x) A= x² + 2x + 1 + 5 - 10x A = x² - 8x +6 B = (2x-3)(3x+1) -2(x+4) B = 6x² + 2x - 9x - 3 - 2x - 8 B = 6x² -9x -11 C= (2x-3)²+(3-2x)(1-x) C = 4x² - 12x + 9 + 3 -3x - 2x + 2x² C = 6x² - 17x + 12

choupydidine

A (x) = (x + 1)² + 5 (1 - 2x) A (x) = x² + 2 * x * 1 + 1² + 5 * 1 + 5 * (- 2x) A (x) = x² + 2x + 1 + 5 - 10x A (x) = x² - 8x + 6 B (x) = (2x - 3) (3x + 1) - 2 (x + 4) B (x) = 2x * 3x + 2x * 1 - 3 * 3x - 3 * 1 - 2 * x - 2 * 4 B (x) = 6x² + 2x - 9x - 3 - 2x - 8 B (x) = 6x² - 9x - 11 C (x) = (2x - 3)² + (3 - 2x) (1 - x) C (x) = (2x)² - 2 * 2x * 3 + 3² + 3 * 1 + 3 * (- x) - 2x * 1 - 2x * (- x) C (x) = 4x² - 12x + 9 + 3 - 3x - 2x + 2x² C (x) = 6x² - 17x + 12

Ajouter une réponse